Introduction of Acrocarpus fraxinifolius-a Fast Growing Species for Social Forestry in Himachal Pradesh - Ghildyal, B. N. (Indian Forester, 1989)
Based on personal observations of character of the species and raising Acrocarpus fraxinifolius in Mandi area of Himachal Pradesh on an experimental basis, it unfolds that with pretreatment of seed in water, the germination is satisfactory. The growth rate is very fast and the species is strongly recommended for Farm Forestry in area of good rainfall like Kangra aDd Balh Valleys and low lying area of Solan, Nalagarh, Kunibar, Jogindernagar, Sarkaghat, Dharmpur and Paonta areas of Himachal Pradesh. It shall meet the requirment of fuelwood, fodder, timber, packing cases and cottage industries like honey bee boxes within a span of short period of 10 years.